2017
DOI: 10.1039/c7ra06914f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of PEI/CS aerogel beads with a high density of reactive sites for efficient Cr(vi) sorption: batch and column studies

Abstract: In view of the sustainable character and high-density of reactive sorption sites, a new kind of poly(ethylenimine)/chitosan (PEI/CS) aerogel beads were successfully synthesized using controllable sol-gel and freeze drying methods, with the aim of using them for efficient Cr(VI) removal from aqueous acid solutions. Compared with the reported CS-based sorbents for hexavalent chromium [Cr(VI)], not only is the synthetic process used simple but the bead-like samples could be easily separated from solutions for rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Those results were consistent with the previous works. 3,21 As can be seen from the Fig. 5b, the uptake capacity of Cr(VI) decreased with the increase of TOC.…”
Section: Effect Of Coexisting Ions and Toc The Effluent Generally Comentioning
confidence: 78%
See 1 more Smart Citation
“…Those results were consistent with the previous works. 3,21 As can be seen from the Fig. 5b, the uptake capacity of Cr(VI) decreased with the increase of TOC.…”
Section: Effect Of Coexisting Ions and Toc The Effluent Generally Comentioning
confidence: 78%
“…Amongst them, using low-cost biomass as adsorbent to remove Cr(VI) has received great attention, such as rice husk, 17 cellulose, 18 lignin, 19 sodium alginate 20 and chitosan. 21 Among these materials, cellulose has received increasing attentions owing to its properties which contain inexpensive, abundant, non-toxic, low weight, renewable and biodegradable. There are many -OH groups on the surface of cellulose that can provide some adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Further application fields embrace environmental remediation and catalysis, both of them have been comprehensively reviewed very recently [210,211]. Functionalized nanofibrillar network of polysaccharide aerogel beads have been utilized as promising reusable filter materials for the applications in environment control system [172,230,231]. High specific surface area of nano-network and chelating functional groups of polysaccharide aerogels offer hosting property and they can be utilized for catalysis applications [65,66,67,68].…”
Section: Applications Of Polysaccharide Aerogel Particlesmentioning
confidence: 99%
“…25–45 Previous studies have identified two main problems in CS/PEI adsorbents used for metal removal: (1) complicated synthesis process 46,47 and (2) reduction in adsorption capacity at pH values above 3 that would lead to low adsorption capacity at neutral pH value. 46–50 To use an adsorbent for chromium removal in industry, the production process should be robust to facilitate scale-up and the adsorbent should be effective at pH values close to real wastewater, instead of highly acidic water.…”
Section: Introductionmentioning
confidence: 99%